2018
DOI: 10.1590/s1677-5538.ibju.2017.0225
|View full text |Cite
|
Sign up to set email alerts
|

Can preoperative neutrophil lymphocyte ratio predict malignancy in patients undergoing partial nephrectomy because of renal mass?

Abstract: Purpose:To evaluate the importance of preoperative neutrophil lymphocyte ratio (NLR) predicting malignancy in patients who undergo partial nephrectomy due to renal mass.Materials and Methods:Seventy nine patients who underwent open partial nephrectomy for renal masses were included in this retrospective study. In preoperative routine blood tests, renal ultrasonography and contrast-enhanced computed tomography were performed for all patients. Preoperative neutrophil lymphocyte ratio were compared in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…We found that the NLR levels were higher in the RCC group, which can reflect the status of the tumor microenvironment. Similarly to our study, a number of researchers have demonstrated that the preoperative NLR value was significantly higher in malignant renal masses compared to benign ones [8,13,14].…”
Section: Discussionsupporting
confidence: 87%
“…We found that the NLR levels were higher in the RCC group, which can reflect the status of the tumor microenvironment. Similarly to our study, a number of researchers have demonstrated that the preoperative NLR value was significantly higher in malignant renal masses compared to benign ones [8,13,14].…”
Section: Discussionsupporting
confidence: 87%
“…Preoperative NLR of the patients with clear cell RCC was significantly higher (p<0.001). However, NLR was not associated with the tumor grade as well as the size of the mass (28).…”
Section: Discussionmentioning
confidence: 76%
“…Identifying pathological properties by preoperative imaging would contribute to reduce unnecessary ureteroscopy biopsy, intraoperative ureteral exploration, and RNU, which might result in tumor cell dissemination ( 3 ). However, using traditional radiological methods to distinguish benign or malignant tumors occasionally lead to inappropriate surgical decisions ( 32 ). It is reported that about 2.9%–12.8% of suspected UUT masses were finally confirmed as benign lesions after RNU ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLR is defined as the ratio of neutrophil to lymphocyte count in peripheral blood ( 32 ). Compared with CTCs, NLR is economic, repeatable, and easy to measure, which could be widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation